Assessment of Salivary Interleukin-1β Levels in Patients with Gingivitis and Periodontitis: An Analytical Cross-Sectional Study - Muntadhr A Al-Musawi; Omar H. Ali (Dental Hypotheses, 2023)
Introduction: The study aimed to analyze the level of salivary Interleukin-1 beta (IL-1β) in subjects with healthy periodontium and patients with gingivitis and periodontitis stage I-III. Methods: A total of 90 individuals participated in the research, separated into five groups, clinically healthy (n = 10), gingivitis (n = 20), stage I periodintitis (n = 20), stage II periodontitis (n = 20), and stage III periodontitis (n = 20). Level of salivary IL-1β was assessed using the enzyme-linked immunosorbent assay. Result: A statically significant difference (P < 0.001) found amongst study groups, further multiple group comparison revealed a statistically significant difference (P < 0.05) when comparing the experimental groups with control and when comparing gingivitis with stage II and III groups. Conclusion: Within the limitations of this cross-sectional study, IL-1β can be considered as a potential salivary biomarkers to differentiate between healthy and unhealthy periodontium.